Management of Venomous Injuries - Haddad, Vidal [UNESP]; Sardenberg, Trajano [UNESP] (My University, 2021)
Injuries caused by venomous animals vary widely in relation to the type of envenomation, depth of envenomation, and severity of the cutaneous necrosis. There are injuries by contact with toxins, which rarely have serious repercussions, while those with inoculated toxins will always be more serious with a direct relation with the depth of the inoculum. When the injuries happen on the hands, these characteristics of the envenomations are maintained. It is a commonly compromised place due to careless contacts with venomous animals. When the necrosis is deep, there are serious complications due to the noble structures and functions of the hands. In this chapter, we try to show the superficial and deep envenomations on the hands and the main therapeutic methods used in these situations.
Keywords: hand injuries; poisonous animals; surgery; toxins; venomous animals